THE THE ACTIVITIES OF ALANINE AMINOTRANSFERASE AND ASPARTATE AMINOTRANSFERASE ENZYMES IN MALE WHITE RATS TREATED WITH EXTRACT ARECA NUT TREATMENT - Kendran, Anak Agung Sagung; Arjana, Anak Agung Gde; Pradnyantari, Anak Agung Sagung Istri (Buletin Veteriner Udayana; Vol. 9 No. 2 Agustus 2017, 2017)
Areca nut is a plant of Arecaceae family, known as herbal medicine and useful as an anthelmetic treatment. The aim of this research was to determine hepar toxicity of the Areca nut extracts given to male white rats by measuring ALT and AST. The doses of extracts were 100 mg/kg, 200 mg/kg, and 400 mg/kg body weight respectively. Data were analyzed by analysis of variance. The results showed that no significant effect of ALT and AST enzymes found in the treatment groups. Betel nut extract in those concentration was not toxic in the male white rats.